Cyclic pseudoelastic training and two-way shape memory behavior of a NiTi alloy with small irrecoverable plastic strains:numerical modeling. (15th May 2021) - Owusu-Danquah, J.S.; Saleeb, A.F.; Soudah, M.A.
Abstract: Novel applications of shape memory alloys (SMAs) in various fields of medicine and engineering necessitate theoretical models that can capture non-inherent material behaviors such as the two-way shape memory effect (TWSME). Most often, this requires the use of completely different sets of models or parameters to distinguish the "virgin" material exhibiting the fundamental behaviors like superelasticity (also known as pseudoelasticity), pseudoplasticity, and one-way shape memory effect, from the "trained" alloy showing the TWSME. Although using a single model (or set of parameters) can provide much insight on the changes within the material during various loading paths and histories from the initial virgin state to the trained state, it is quite challenging. In this study, an attempt was made to use a developed general multi-mechanism material model and a single set of parameters to predict both the inherent pseudoelastic behavior and non-intrinsic two-way shape memory effect characteristics of a NiTi shape memory alloy. To this end, several simulations were carried out to investigate the effect of pseudoelastic training conditions on the corresponding actuation strain, cyclic stability, and transformation temperatures of the NiTi under zero-load TWSME. Whilst previous studies considered external indicators such as the magnitude of plastic or irrecoverable strain as a prerequisite for TWSME, the present model focused primarily on internal stresses. Based on the magnitude of the zero-load actuation strain (measured from the trained material under no external load), the model results indicated that the magnitude of the pseudoelastic training strain (in comparison to the training temperature, and the number of training cycles) has a pronounced effect on the cyclic TWSME actuation characteristics. Moreover, observations from the internal state (hidden) variables of the model, representing the intrinsic residual stress state in the trained material (under zero observable/external stress) showed the possibility for an SMA to generate TWSME even if there is no significant accumulation of permanent strains.